Association between pseudoexfoliation and Alzheimer’s disease-related brain atrophy - Won Cheol Jeong; Jin-Young Min; Tae Gu Kang; Heewon Bae (PLoS ONE, 2023)
Background/aims Pseudoexfoliation (PEX) syndrome is an age-related disorder characterized by the accumulation of extracellular material in the anterior eye segment. PEX pathogenesis is not fully understood, but amyloid which accumulates in the brain of patients with Alzheimer’s disease (AD) is a PEX component. PEX deposition shares features with amyloid aggregation in AD, and brain atrophy is a common AD feature, with β-amyloid accumulation among contributing factors. This study investigated whether PEX syndrome is associated with AD-related brain atrophy. Methods We reviewed the medical records of patients diagnosed with PEX at the Veterans Health Service Medical Center between January 2015 and August 2021. This retrospective cohort study included 48 patients with PEX and 48 healthy age- and sex-matched controls. Patients with PEX were divided into two groups: with and without glaucoma. The main outcome measure was brain atrophy, using a visual rating scale, and AD incidence. Brain atrophy was measured using the Scheltens scale for medial temporal atrophy, the posterior cortical atrophy scale for parietal atrophy, and the Pasquier scale for global cortical atrophy. Results The percentage of participants with medial temporal atrophy was 56.3% in the PEX group and 35.4% in the control group. The global cortical atrophy and parietal atrophy scores were significantly higher in the PEX group (P<0.05), whereas the PEX and PEX glaucoma groups showed no difference. Among the 96 participants, 16 and 5 participants in the PEX and control groups, respectively, were diagnosed with dementia. Patients with PEX glaucoma tended to have lower Mini-Mental State Examination scores, indicating impaired cognitive function, than those without glaucoma. Conclusion PEX is associated with brain atrophy, reflecting the risk of developing AD. Patients with PEX glaucoma may present with advanced AD stages. Our results suggest that PEX may be a predictor of AD.